I don't know how to work this problem 3(-6)-7 over -3 to the second power -4 to the second power

3(-6)-7 over -3 to the second power -4 to the second power

which is

= [3(- 6) - 7] / (-3)^2 * (-4)^2

Now we solve for powers. then

= [3(- 6) - 7] / 9 * 16 [ As (-3)^2 = 9 and (-4)^2 = 16 ]

Now We solve for the upper brackets then

= [- 18 - 7] / 144

Now

= - 25 / 144

Hence [3(- 6) - 7] / (-3)^2 * (-4)^2 = - 25 / 144

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up